Evaluation of resilience engineering using super decisions software - Gholam abbas Shirali; Leila Nematpour (Tabriz University of Medical Sciences, 2019)
Background: Resilience engineering (RE) is a new approach to upgrade safety management systems. Due to its novelty in the field of safety, RE seems to be promising in providing good indicators to assess priorities in organizational strengths/weaknesses while planning to promote safety within organizations. Several methods have been recently developed to evaluate REperformance. The current study is an attempt to quantify and determine the priorities of REdimensions in a steel industry using analytic network process (ANP). Methods: In this cross-sectional study, 489 male workers of a steel industry participated. Forthis purpose, the RE questionnaire was distributed among workers and, then, super decisions software (version 3.2) was used to analyze the data. Results: The results indicated that there was a sufficient level of RE in the organization where top management commitment with normalized weight 0.1781 and awareness-opacity with normalized weight 0.1483 were ranked as the first and last priorities of the organization, respectively. Conclusion: The results of this study showed that the top management system, with the adoption of safety policies, has been able to improve the performance of RE in the organization. Managers should consider appropriate measures to improve the RE situation.